A Series of Cube-Shaped Polyoxoniobates Encapsulating Octahedral Cu12XmOn Clusters With Hydrolytic Decomposition for Chemical Warfare Agents - Wu, Yan-Lan; Zhang, Rong-Tao; Sun, Yan-Qiong; Li, Xin-Xiong; Zheng, Shou-Tian (Frontiers in Chemistry, 2020)
A series of cube-shaped polyoxoniobates, MCu12O8)(Cu12XmOn)(Nb7(OH)O21)8 (M = Nb(1, 2), Ln3+(3), X = I(1, m=3, n=3; 2, m=5, n=1), Br(3, m=5, n=1) have been synthesized. As the first octahedral Cu12XmOn cluster incorporated polyoxoniobate, the cube-shaped three-shell structure of MCu12O8)(Cu12XmOn)(Nb7(OH)O21)8 polyanion contains a MCu12O8 body-centered cuboctahedron, a Cu12XmOn octahedron and a Cu12(Nb7(OH)O21)8 cube. Compounds 1, 2, 3 show effective catalytic activities for hydrolytic decomposition of chemical warefare agent simulants.